Analisa Tingkat Kepuasan Mahasiswa Terhadap Perkuliahan Daring Pada Era Pandemi COVID-19 - Dodi Sukma R.A; Roki Hardianto; Heleni Filtri (Universitas Lancang Kuning, 2021)
Online learning is learning that uses the internet network with accessibility, connectivity, flexibility, and the ability to bring up various types of learning interactions. Satisfaction is a person's feelings of pleasure or disappointment that arise after comparing his perceptions/impressions of the performance or results of a product and his expectations. Research on student perceptions of online learning is limited to aspects of teaching and learning, the ability of lecturers, facilities and infrastructure. To get results from the perception or opinion of a student from the level of satisfaction of online lectures, it can be done using the Fuzzy logic mamdani method and for calculations using the Slovin formula.